Five weeks of heat training increases haemoglobin mass in elite cyclists - Rønnestad, B. R.; Hamarsland, H.; Hansen, J.; Holen, E.; Montero, D.; Whist, J. E.; Lundby, C. (Experimental Physiology, 2021)
In this study we tested the hypothesis that performing 1 h of regular light exercise in a heat chamber (HEAT; 37.8 ± 0.5°C; 65.4 ± 1.8% humidity) 5 times week-1 for a total of 5 weeks increases haemoglobin mass (Hbmass) and exercise performance in elite cyclists (urn:x-wiley:09580670:media:eph12783:eph12783-math-0001 = 76.2 ± 7.6 ml min-1 kg-1). Twenty-three male volunteers were assigned to HEAT (n = 11) or CON (n = 12; 15.5 ± 0.1°C; 25.1 ± 0.0% humidity) training groups. Hbmass was determined before and after the intervention period in conjunction with an extensive exercise test protocol (conducted at 16-19°C). HEAT increased (P < 0.05) Hbmass by 42 g from 893 ± 78 to 935 ± 108 g whereas Hbmass remained unchanged (+6 g) in CON. Furthermore, statistical analysis revealed a time-group interaction (P < 0.05). The greater increase in Hbmass in HEAT, however, did not manifest in a greater increase in urn:x-wiley:09580670:media:eph12783:eph12783-math-0002 (225 ± 274 ml min-1 in HEAT and 161 ± 202 ml min-1 in CON). While HEAT reduced (P < 0.05) lactate levels during some of the submaximal exercise tests, there was no statistical difference between other performance parameters. There were, however, small to intermediate effect sizes favouring HEAT for lactate threshold power output (2.8 ± 3.9 vs. -0.4 ± 5.1% change, effect size (ES) = 0.34), gross economy in the fatigued state (0.19 ± 0.42 vs. -0.12 ± 0.49%-point change, ES = 0.52) and 15 min mean power (6.9 ± 8.4 vs. 3.4 ± 5.1% increase, ES = 0.22). This study demonstrates an increase in Hbmass and small to intermediate effect sizes on exercise variables in elite cyclists following a 5-week heat training intervention.